Challenges of inclusion with regards to early childhood education learners: the case of Mabula primary school in Mzilikazi district in Bulawayo Metropolitan Province. - Ncube, Joyce (Midlands State University, 2019)
This research project sought to find the challenges faced by teachers and learners at ECE level in the school, then find solutions to the challenges. Questionnaires, interviews and focus group discussions were used to collect data for this research. The researcher investigated from parents on the challenges faced by both the teacher and the learner in an inclusive setting and also what their recommendations were concerning the challenges that were raised. The findings from the data collected pointed out that there were challenges faced by both teachers and learners at the school as inclusion was being implemented. The challenges comprised of inadequate infrastructure, improper infrastructure, inadequate material resources, and lack of funds to promote IE, lack of teacher expertise, adoption of a result oriented curriculum, lack of a proper policy on inclusion and negative attitudes. The recommendations advocated for alleviating the challenges observed included staff developing teachers, conducting workshops for teachers, sensitising both parents and learners, prioritising funds in favour of IE, improving infrastructure, employing assistant teachers in the ECE department and making use of the learner exit profiles.